It’s Who We Are: New Approaches, Supported by Evidence - Jack Elliot; Jessica R Spence; Ignacie Tumushime; Meikah Dado; Ana Casas; Olawunmi Ilesanmi; Megan Gould; Mathilde Le Bon (Journal of International Agricultural and Extension Education, 2022)
This issue poses the question, “Where do we go from here?” Agricultural and extension educators are well equipped to grow, reimagine, and improve our work. First, we go to our foundational training and educational background and apply those key principles in a new contextual setting. 1) Although we never left the country, we built a virtual study abroad using Kolb’s model (1984) of experiential learning to incorporate all four phases into our VHIE teaching and learning process. 2) Creating the SPS Policy Framework for Africa introduced our team to the Continental SPS Committee, which provided credibility to conduct two virtual 4-day participatory workshops to initiate the strategic plans for food safety and plant health. 3) When we addressed the impact of COVID-19 in Africa, we employed the most fundamental, important, and effective educational attribute, caring. 4) Conference attendance improved during the pandemic. However, agricultural and extension educators don’t view virtual meetings as a replacement for in-person meetings. 5) Students who have intercultural competence are in high demand. Lewin's Theory of Planned Change explains the virtual student exchange rapid growth phenomena. The increase in students of color and low SES within intercultural competency programs is a welcome benefit. The problems that COVID-19 brought upon the globe challenged our educational, extension, and outreach systems. I observed that agricultural and extension educators utilized their foundational delivery background and talents to adjust quickly to the contextual COVID-19 pandemic world. We grew, reimagined, and improved our delivery and outreach because that is who we are.
Keywords: Extension Delivery Systems; Virtual Exchange; Participatory Approach